Effect of Primary Interference on Cognitive Relay Network - Sadeghi, Nafise; Aghajani, Rouhollah (Ciência e Natura, 2015)
Cognitive relay network is a method for optimizing frequency spectrum utilization. What’s important in these networks is to transmit data such that none of primary and secondary users cause destructive interference to other users. Although primary interference affect cognitive network performance, but is neglected in former researches. In this paper, we show cognitive network performance by calculating outage probability. We consider both primary and secondary interference links. Finally, our study is corroborated by representative numerical example. Simulation results demonstrate that increasing interference threshold increase outage probability and increasing data transmit rate cause outage probability increase.